Efektivitas Metode Bercerita (Storytelling) dalam Pembelajaran PKn untuk Menanamkan Karakter Kebangsaan - Herliyanto, Muci (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2023)
This study aims to determine the effectiveness of the storytelling method in Civic Education (PKn) learning to instill national character in elementary school students. The research uses a library research method with the object of study being theories and findings from academic journals related to storytelling in character education, and the subjects are elementary school students. Data were collected through documentation studies of scientific articles, books, and research reports from the last five years. The data were analyzed using qualitative content analysis techniques. The results show that storytelling is effective in instilling national values such as patriotism, tolerance, and unity in Civic Education learning. Students' emotional engagement, teacher creativity in delivering stories, and the relevance of stories to local contexts are supporting factors of this method’s effectiveness. It is concluded that storytelling is a relevant and engaging pedagogical approach for shaping students' national character in elementary schools